A Self-Aligned, Solution-Processed Low-Voltage Operated Organic Thin-Film Transistor for Ammonia Gas Sensing at Room Temperature - Verma A.; Mishra V.N.; Prakash R. (My University, 2025)
In this article, a self-aligned, cost-efficient, fully solution-processed, and low-voltage operated high-k dielectric-based p-channel organic thin-film transistor (OTFT) has been developed and investigated for toxic ammonia analyte at room temperature (RT - 25 °C). A spin casting method has been utilized to deposit a high-k dielectric, lanthanum zirconium oxide (LaZrOx), on a p++ silicon substrate. The organic semiconductor channel deposition uses minimal wastage self-assembly floating film transfer method for poly(3-hexylthiophene-2,5-diyl) (P3HT) growth over hexamethyldisilazane (HMDS)-treated LaZrOx dielectric. The doping of lanthanum in ZrOx material reduces the charge traps and rms surface roughness and also minimizes the other surface defects and carrier scattering at the dielectric interface. The solution-processed dielectric material is suitable for low-voltage operated OTFT due to its high capacitance per unit area of 486 nF/cm2 at 1 kHz and a low leakage current density of ∼ 0.5× 10-8 A/cm2 at -2 V. Even at a low operating voltage of -2 V, the fabricated OTFT is capable of producing a good saturated current. The OTFT sensor results in a high response of 47% at 5 ppm NH3 analyte and a low detection limit of 11.65 ppb. The developed sensor exhibits a low average response and a recovery time of 9 and 50 s and is almost independent of relative humidity variations in the range of 30%-70%. The study reveals that this novel low-voltage OTFT device is capable of operating at -2 V and has shown a high sensitivity toward ammonia gas detection at RT. © 2001-2012 IEEE.